2021
DOI: 10.1021/acsestwater.1c00010
|View full text |Cite
|
Sign up to set email alerts
|

Application of Zn Isotope Compositions in Oysters to Monitor and Quantify Anthropogenic Zn Bioaccumulation in Marine Environments over Four Decades: A “Mussel Watch Program” Upgrade

Abstract: The application of zinc (Zn) isotope compositions in bivalve organisms to quantify anthropogenic Zn bioaccumulation in marine biota is of great interest to environmental marine management programs such as the "Mussel Watch Program". Field studies, however, are urgently needed to test its practical value. To this end, we investigated Zn isotope variations in the oyster Crassostrea gigas collected over four decades near the Loire estuary (France), where previous geochemical studies provided evidence for a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…For example, if metals are supplied to the ECS by atmospheric deposition via a pathway independent of CDW, it becomes a new end member. Zinc likely has an additional endmember because anthropogenic Zn is observed in various environments, including rivers and the atmosphere (Araújo et al, 2021;Chen et al, 2008;Dong, 2017;Souto-Oliveira et al, 2018). Furthermore, reduction of Mn oxides releases adsorbed trace metals, which is a potential source of trace metals.…”
Section: Mixing Of Dissolved Metals In the East China Seamentioning
confidence: 99%
“…For example, if metals are supplied to the ECS by atmospheric deposition via a pathway independent of CDW, it becomes a new end member. Zinc likely has an additional endmember because anthropogenic Zn is observed in various environments, including rivers and the atmosphere (Araújo et al, 2021;Chen et al, 2008;Dong, 2017;Souto-Oliveira et al, 2018). Furthermore, reduction of Mn oxides releases adsorbed trace metals, which is a potential source of trace metals.…”
Section: Mixing Of Dissolved Metals In the East China Seamentioning
confidence: 99%
“…2). [58][59][60][61] Metal isotope profiles of dated sediment cores are useful to verify anthropogenic contamination evolution across time (Fig. 2), [62][63][64][65][66][67] while surface sediments enable mapping the recent dispersion of metal contaminants.…”
Section: Anthropogenic Source Apportionments and Metal Contamination ...mentioning
confidence: 99%
“…Conversely, a method using isotopes as tracers of metal sources in bivalves may be effective. Shiel et al (2012Shiel et al ( , 2013 and Araújo et al (2021) demonstrated that Cd, Zn, and Pb isotopes are successfully used to trace their sources in bivalves collected from the coasts of western Canada, the USA, and France. Among these isotopes, Pb isotopes have been widely used as a well-known "fingerprinting" tool to evaluate the sources of Pb in various environmental samples, including aerosols, water, sediment, and biota, because they are not fractionated in nature (Shiel et al, 2012(Shiel et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%